2009
DOI: 10.1108/09604520910971539
|View full text |Cite
|
Sign up to set email alerts
|

E‐service quality: comparing the perceptions of providers and customers

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 35 publications
0
29
0
2
Order By: Relevance
“…Shachaf et al (2008) and Wolfinbarger and Gilly (2003) argue that reliability is the strongest predictor of customer satisfaction in electronic channels. In online transactions, Stiakakis and Georgiadis (2009) found reliability as the fundamental criterion of superior electronic service quality. Within ATMs, both Khan (2010) and Katono (2011) found reliability to be an essential ATM quality dimension which influences customer satisfaction.…”
Section: Atm Quality and Customer Satisfactionmentioning
confidence: 99%
“…Shachaf et al (2008) and Wolfinbarger and Gilly (2003) argue that reliability is the strongest predictor of customer satisfaction in electronic channels. In online transactions, Stiakakis and Georgiadis (2009) found reliability as the fundamental criterion of superior electronic service quality. Within ATMs, both Khan (2010) and Katono (2011) found reliability to be an essential ATM quality dimension which influences customer satisfaction.…”
Section: Atm Quality and Customer Satisfactionmentioning
confidence: 99%
“…Research has shown that service quality, whether through traditional or electronic channels, have different dimensions (Parasuraman et al, 1988(Parasuraman et al, , 2005Shachaf et al, 2008;Nusair and Kandampully, 2008;Stiakakis and Georgiadis, 2009). Some previous studies on e-banking service quality have followed the view that customers use e-banking channels in a complementary way and therefore, their service quality dimensions were jointly determined in a single study ( Joseph and Stone, 2003;Al-Hawari and Ward, 2006).…”
Section: Electronic Service Qualitymentioning
confidence: 99%
“…За евалуацију његовог нивоа у сектору промета воћа и поврћа, Rossi Scalco и сарадници (2014), ослањајући се на SERQUAL модел, анализирали су доступност производа као једну од варијабли поузданости услуге малопродавца. Такође, она је разматрана и као један од критеријума поузданости квалитета електронске услуге (Stiakakis, Georgiadis, 2009). При томе, имајући у виду да су за купце веома значајне информације о доступности производа, она је у оквиру димензије поузданости "инкорпорирана" у критеријум "тачност информација".…”
Section: преглед литературеunclassified